2017
DOI: 10.2147/ott.s121472
|View full text |Cite
|
Sign up to set email alerts
|

<em>MTHFR C677T</em> polymorphism and breast, ovarian cancer risk: a meta-analysis of 19,260 patients and 26,364 controls

Abstract: ObjectivePrevious studies have found that many gene variations can be detected in both breast cancer and ovarian cancer, which is beneficial for the elaboration of the molecular origin of breast and ovarian cancer. Furthermore, many studies have explored the association of methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism with the risk of breast cancer and/or ovarian cancer; however, the results remained inconclusive. Therefore, this study conducted a systematic review and meta-analysis to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 71 publications
5
39
0
Order By: Relevance
“…Epidemiological studies had identified that Methylene tetrahydrofolate reductase (MTHFR) was a potential genetic marker of different malignancies (Yi et al, 2016;He and Shen, 2017). The human MTHFR gene is located on chromosome 1p36.3, consist of 11 exons and spans 2.2 kb of genomic DNA (Abedinzadeh et al, 2015;Azarpira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies had identified that Methylene tetrahydrofolate reductase (MTHFR) was a potential genetic marker of different malignancies (Yi et al, 2016;He and Shen, 2017). The human MTHFR gene is located on chromosome 1p36.3, consist of 11 exons and spans 2.2 kb of genomic DNA (Abedinzadeh et al, 2015;Azarpira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, a large number of epidemiological studies and meta-analyses have evaluated the association between the MTHFR 677C>T polymorphism and susceptibility to ovarian and cervical cancer (Yi et al, 2016;He and Shen, 2017). However, the results were conflicting and inconclusive, presumably due to small sample size in each published study, various genetic backgrounds and possible selection bias (He and Shen, 2017). Subsequently, a few novel studies have recently been performed to estimate the associations of MTHFR 677C>T polymorphism with risk of ovarian and cervical cancer and provide new evidences that were not included in the previous meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme methylenetetrahydrofolate reductase (MTHFR) has an important role in the regulation of methionine and homocysteine concentrations in folate metabolism . Individuals with the MTHFR 677TT variant genotype possessed a twofold increased CGA risk (OR = 2.04)…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Reports have demonstrated that MTHFR C677T polymorphism is associated with other pathologies . On the other hand, there is no consensus on the effect of this polymorphism in the susceptibility to CLL .…”
Section: Descriptive Statistics Of Clinical Data and Summary Of Genotmentioning
confidence: 99%
“…Moreover, the mutant genotype conditions an enzyme with only 30% enzymatic activity when compared to wild‐type . Thus, the lower enzymatic activity contributes to hypomethylation leading to lower levels of circulating 5‐MTHF and increasing the plasma homocysteine levels . Therefore, the hyperhomocysteine promotes inflammatory processes via oxidative stress, cytokines, and chemokines, which may contribute to the carcinogenesis process .…”
Section: Descriptive Statistics Of Clinical Data and Summary Of Genotmentioning
confidence: 99%